2015
DOI: 10.4238/2015.may.11.29
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artemisia annua polysaccharides as an adjuvant to hepatitis C vaccination

Abstract: ABSTRACT. The traditional Chinese medicine Artemisia annua can prevent and treat hepatitis following an unclear mechanism. The aim of this study was to evaluate the effects of A. annua polysaccharides (AAP) on hepatitis C virus (HCV). A pcDNA3.1/NS3 expression vector was constructed. Ninety female BALB/c mice were randomly divided into six groups: high-dose AAP (1 mg/mL) + HCV/NS3 plasmid; middle-dose AAP (0.5 mg/mL) + HCV/NS3 plasmid; lowdose AAP (0.1 mg/mL) + HCV/NS3 plasmid; HCV/NS3 plasmid; high-dose AAP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, Behzadi et al have shown in their study that the use of complete Freund’s adjuvant, monophosphoryl lipid A can induce the production of Th1/Th2 cells and CD8+ T-cells in all the immunized groups [ 26 ]. Interestingly, an eccentric study on vaccine development have shown that polysaccharides derived from Artemisia annua could be utilized as an adjuvant and modulate immune response induced by a NS3 plasmid DNA vaccine by increasing IFN-γ but not antibody or IL-4, suggesting the mechanism to be the result of modulation of Th1 response [ 44 ]. Synthesized Poly(D,L-lactic acid)-co-poly(ethylene glycol)-co-poly(D,L-lactic acid) (PLA–PEG–PLA) and poly(d,l-lactic-co-glycolic acid;PLGA)–PEG–PLGA used as micelles with encapsulated plasmid pcDNA3.1 also had appealing results as adjuvants with no considerable side effects in single oral immunization with DNA/polymers with noticable immune responses in in vivo tests [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Behzadi et al have shown in their study that the use of complete Freund’s adjuvant, monophosphoryl lipid A can induce the production of Th1/Th2 cells and CD8+ T-cells in all the immunized groups [ 26 ]. Interestingly, an eccentric study on vaccine development have shown that polysaccharides derived from Artemisia annua could be utilized as an adjuvant and modulate immune response induced by a NS3 plasmid DNA vaccine by increasing IFN-γ but not antibody or IL-4, suggesting the mechanism to be the result of modulation of Th1 response [ 44 ]. Synthesized Poly(D,L-lactic acid)-co-poly(ethylene glycol)-co-poly(D,L-lactic acid) (PLA–PEG–PLA) and poly(d,l-lactic-co-glycolic acid;PLGA)–PEG–PLGA used as micelles with encapsulated plasmid pcDNA3.1 also had appealing results as adjuvants with no considerable side effects in single oral immunization with DNA/polymers with noticable immune responses in in vivo tests [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glycoproteins are the active components of AMK protein extract and its immune stimulating activity is due to the carbohydrate, rather than protein residues AMK extract showed two major groups of bands around 27 kDa and smaller than 15 kDa together with a broad spectrum of molecular weights by CBB staining and mainly of approximately 200, 27, and 13 kDa by Schiff reagent staining [Fig. 6 In summary, glycoproteins and polysaccharides derived from traditional medicines could be potentially used as efficacious vaccine adjuvant candidates or adjuvant boosters (Bao et al, 2015;Pi et al, 2014). The current findings highlight that AMK extracts, especially protein extract, are useful as adjuvant and/or adjuvant booster to improve the efficacy of vaccination by enhancing systemic immune response.…”
Section: Amk Samples Improves the Protective Immunity Against A Pleuropneumoniae Infection By Stimulating Systemic Antigen-specific Immunmentioning
confidence: 99%
“…Results of a study by Bao et al suggested that an extract of A. annua, when used as an adjuvant of HCV/Nonstructural protein 3 (NS3) DNA vaccine, increased antibody levels in vivo and promoted IFN-γ secretion by increasing a Th1-type cellular immune response (48). Galla chinensis, also called Wu-BeiZi, is a TCM that is commonly used to treat dysentery, bleeding, coughing, sweating, and rectal prolapse.…”
Section: Extracts In and Formulations Of Tcms To Treat Hcvmentioning
confidence: 99%